PERBAIKAN LINTASAN PRODUKSI DENGAN PENERAPAN LARGE CANDIDATE RULE (LCR) DAN KILLBRIDGE AND WESTER PADA PROSES PRODUKSI DI PT EJ - Aditya Fahmi Nurwicaksono; Rusindiyanto Rusindiyanto (UPN Veteran Jawa Timur, 2020)
PT. EJ is a company that manufactures stoves. Problems experienced by PT. EJ, the production line is not optimal. As a result this has resulted in waiting times at several existing work stations. This phenomenon occurs due to the inability of companies to control production trajectory times and improper allocation of machinery and human resources. The purpose of this study is to determine a balanced production line at PT. EJ to produce optimal production processes. The method used to support the purpose of this study is the Large Candidate Rule (LCR) and Killbridge & Wester methods. As a reference method with the highest recommended path efficiency results. The results of research conducted at PT. EJ is a condition that currently runs channel efficiency reaching 68.85%, delays in balance 31.15% and smoothness index 19.065 with the number of work stations 9. After the Killbridge & Wester method is applied, the channel efficiency value increases by 77.46 %, delays in balances decreased to 22.54% and the smoothness index increased at 10.76 with 8 work stations.